2013
DOI: 10.1158/1078-0432.ccr-13-1049
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2-ERG Status Is Not Prognostic Following Prostate Cancer Radiotherapy: Implications for Fusion Status and DSB Repair

Abstract: Background: Preclinical data suggest that TMPRSS2-ERG gene fusions, present in about 50% of prostate cancers, may be a surrogate for DNA repair status and therefore a biomarker for DNA-damaging agents. To test this hypothesis, we examined whether TMPRSS2-ERG status was associated with biochemical failure after clinical induction of DNA damage following image-guided radiotherapy (IGRT).Methods: Pretreatment biopsies from two cohorts of patients with intermediate-risk prostate cancer [T1/T2, Gleason score (GS) <… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 52 publications
2
26
0
Order By: Relevance
“…Here we extend these observations by showing that there was no difference in DNA damage initiation as indicated by activation of ATM and Comet assays. Clinical data indicating that TMPRSS2-ERG is not prognostic for following PCa radiotherapy (44) support this conclusion. A recent study found that ERG expression conferred a small enhancement in radio-sensitization (45).…”
Section: Discussionmentioning
confidence: 95%
“…Here we extend these observations by showing that there was no difference in DNA damage initiation as indicated by activation of ATM and Comet assays. Clinical data indicating that TMPRSS2-ERG is not prognostic for following PCa radiotherapy (44) support this conclusion. A recent study found that ERG expression conferred a small enhancement in radio-sensitization (45).…”
Section: Discussionmentioning
confidence: 95%
“…In a recent publication, Dal Pra and colleagues (42) looked at ERG status alone in pretreatment biopsies in patients with prostate cancer treated by image-guided radiotherapy (IGRT), and identified no association between ERG status and biochemical-free relapse rate. Another study reported that tumors with c-MYC amplification alone, or combined with PTEN loss, were prognostic for BCR after IGRT (32).…”
Section: Discussionmentioning
confidence: 99%
“…So far, no specific inhibitors of ERG function have been described. In a recent report two independent cohorts of over 100 patients were treated with external beam radiotherapy (Dal Pra et al 2013). Although preclinical studies predicted that TMPRSS2-ERG tumors might be more sensitive to radiation (Brenner et al 2011), the presence of the gene fusion showed no association with biochemical recurrence-free survival in the clinical study.…”
Section: Ets Fusions As Diagnostic and Prognostic Markers Of Prostatementioning
confidence: 99%